PERANCANGAN SISTEM TRANSAKSI ONLINE PADA E-COMMERCE MENGGUNAKAN TEKNOLOGI WEB SERVICE (STUDI KASUS DESA MLATIHARJO KABUPATEN DEMAK) - Rendra Bagus Setiawan; Rudy Latuperissa; Suprihadi Suprihadi (Universitas Kristen Duta Wacana, 2014)
Economy development policy in Indonesia focuses on increasing local or regional economy, especially the real sector including trade sector. One of the problems today is how to improve and strengthen the region potential, for example cooperatives, SMEs and cluster in using information technology such as e-Commerce. Therefore, this research designs online transaction system on e-Commerce using web service technology. The case study used in the process of design is Mlatiharjo village in Demak because it has the predicate of innovative village of agriculture. This system is developed using prototyping method and implemented using PHP 5 technology, MySQL database and supported by web service SOAP technology. Thus, online transaction system in the e-Commerce is able to manage and control authority for the village potential. By facilitating this village with the developed system, every people in the village could contribute to the commerce transaction of their products.